Worker Health Monitoring Through Whole Body Counter Examination for Safety and Radiation Protection (2017-2018 Data) - Surniyantoro, Harry Nugroho Eko; Sugiyana, Sugiyana; Prasetio, Heru; Ikram, Abarrul; Syaifudin, Mukh (KEMAS: Jurnal Kesehatan Masyarakat, 2021)
Abstract. Radiation protection is an action or effort taken to reduce the effects of damaging radiation exposure. Therefore, it is necessary to routinely monitor the condition of workers, among others, with a whole-body counter (WBC) either for daily activities or in a radiation emergency. In this research 78 male and female workers with an average age of 44.51 years who have been worked for 1 up to more than 30 years at the Center for Technology of Radiation Safety and Metrology (PTKMR) - BATAN in 2018-2019 have been determined with standard procedures. The results showed that the average K-40 count for the year 2018 was 3767.35 ± 975.33 Bq. Among the 80 participants tested, internal radioisotopic contamination with Cs-137 was detected in one person, but the levels were marginal and just exceeded the detection limit (250 Bq/body). This average value was lower than that of the previous year (2017) i.e. 4274.74 ± 740.85 Bq for 43 respondents. There is no positive correlation between radioactivity with the bodyweight of respondents but correlated positively with body mass index. It was concluded that the radioactivities of the workers of PTKMR are still within a normal range.